AI-Powered Vision System for the Correction of an Axxon Adhesive Dispenser for SMT in an Industry of the Manaus Industrial Pole – PIM - Luniere Brito, Hallisom (2025)
This paper presents the development and application of an intelligent system based on computer vision and artificial intelligence for monitoring and automatic correction of the adhesive application process on printed circuit boards (PCB) in the electronics industry. The adhesive application process is essential for the precise fixing of components, and eventual failures can compromise the quality and performance of the final products. To automate visual inspection and reduce the occurrence of human errors, a convolutional neural network (CNN) model trained with real images of the production line was developed, capable of identifying correct patterns and failures in the application of the adhesive. The system integrates high-resolution cameras, image processing software and a control interface, enabling real-time monitoring and the execution of automatic corrective actions. The results obtained demonstrate the effectiveness of the proposed system, with a high level of accuracy in detecting faults, contributing to improving the quality of the production process and aligning with the principles of Industry 4.0. The research concludes that the adoption of intelligent systems based on computer vision represents a significant advance for quality control in the manufacturing of electronic devices.